2015
DOI: 10.1021/acs.jced.5b00053
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Measurement and Modeling for the NaCl–NH4Cl–Monoethylene Glycol–H2O System from (278 to 353) K

Abstract: The solubilities of NH 4 Cl and NaCl in the mixtures of monoethylene glycol (MEG) and water were determined, respectively, in the temperature range of (278 to 353) K by a dynamic method. The NaCl− NH 4 Cl−MEG−H 2 O system with MEG mole fraction of 0.30 on a salt-free basis was also investigated from (278 to 353) K to determine its phase equilibrium as a function of temperature and the concentration of electrolytes. The solubilities of both NH 4 Cl and NaCl in the MEG−H 2 O mixtures were found to decrease with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…This dependence has been carefully determined, as it may be better appreciated in the zoomed region inside Figure . This NaCl solubility temperature trend is also in accordance with the measurements reported by Baldwin et al and Zeng and Li only for pure MEG. Nonetheless, this reverse behavior was not previously described for MEG aqueous mixtures.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This dependence has been carefully determined, as it may be better appreciated in the zoomed region inside Figure . This NaCl solubility temperature trend is also in accordance with the measurements reported by Baldwin et al and Zeng and Li only for pure MEG. Nonetheless, this reverse behavior was not previously described for MEG aqueous mixtures.…”
Section: Resultssupporting
confidence: 93%
“…A reverse temperature dependency of the NaCl solubility was only observed in pure MEG. 14,15,18 In all cases, it was demonstrated that the solubility of NaCl decreases considerably with MEG concentration. Djamali et al 19 measured solubility data for sodium chloride in aqueous mixtures of MEG in the temperature range of 297−467 K at 6.45 MPa.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations